Acts of vengeance [videorecording (Blu-Ray)] - Venne, Matt, 1974-; Banderas, Antonio; Urban, Karl, 1972-; Vega, Paz, 1976-; Dyer, Clint, 1968-; Serafini, Cristina; Blankenship, Lillian; Srebrev, Atanas; Smith, Mark Rhino; Vasilev, Raycho; Clickner, Stacey; Forster, Robert, 1942-2019; et al. (Lionsgate, 2017)
A fast-talking lawyer transforms his body and takes a vow of silence, not to be broken until he finds out who killed his wife and daughter and has his revenge.